Sistem Pendukung Keputusan Penentuan Dosen Pembimbing Skripsi Menggunakan Metode Profile Matching (Studi Kasus : STMIK Pelita Nusantara Medan) - Bosker Sinaga; Yulia Utami (Jurnal Mantik Penusa, 2018)
The determination of the thesis supervisor is very important to note for maximizing the results of the thesis. In the process of completing the thesis, students are usually assisted by a supervisor to direct the completion of the thesis. In determining the supervising lecturer, it must be very concerned, especially according to the field. The determination of the supervisor is determined by the Head of the Study Program, the work must be considered so that it takes time to adjust the thesis title and the expertise of the lecturer. The system that is needed is the Decision Support System for Determining Thesis Supervisors. Making this system starts from observing and searching data, analyzing data to determine aspects and criteria, then design the application flow, database design, design the user interface and then build the system with Microsoft Visual Studio 2010 and MySQL applications for its database. The final result of this research is to produce a decision support system to determine the thesis supervisor by applying the profile matching method.